Warren, Gouverneur Kemble (Tufts Archival Research Center, 2008)
2.5 x 4.25. "Warren, Gouverneur Kemble 1830-1882; Major-gen'l (Union Army) Mar. 13, 1865- ." Produced by: Joseph Ward, 125 Washington Street, Boston. These dates are approximate.